Additive contribution of multiferroic film and semiconductor substrate from nanotube array to resistive switching, topographic features - Shikhgasan Ramazanov; Gaji Gajiev; Daud Selimov; Sadrudin Gadzhimuradov; Sagim Suleymanov; Ştefan Ţălu; Robert S. Matos; Henrique D. da Fonseca Filho (Modern Electronic Materials)
The structure BiFeO3/TiO2–NTs (BFOT) obtained using the atomic layer deposition. During the Anatase/Rutile phase transformation; there is a redistribution of Fe/Ti atoms, resulting in the formation of local inhomogeneities and charge trapping centres. Studies of the resistive switching effect showed nonlinear current-voltage characteristics. The negative differential resistance probably arises from the oxide dielectric layer of BFO, thin regions of which participate in the tunneling process. The BFOT surface exhibits topographic variations with spatial patterns that conform to normality, and the distribution of topographic heights displays a quasi-normal behavior. The self-affine attributes of the BFOT film are validated by the exponential reduction in autocorrelation functions, and the Minkowski functionals underscore the intricate and irregular nature of the film's topographic patterns.